Students’ Perception of The Implementation of Kampus Mengajar - Sintiya, Kharisma Devi; Muchyidin, M. Syasichul; Asyhar, Wildan Isna (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
The 2020-launched MBKM programme, which was managed by the Ministry of Education and Culture, included the Kampus Mengajar. Students gained a creative attitude, teamwork abilities, and work preparation through this programme, which benefited the neighbourhood. The purpose of this study was to analyze how students felt about the introduction of Kampus Mengajar. This study design is qualitative descriptive research, using qualitative methods like interviewing and documenting to gather data. The participants in Kampus Mengajar 4 served as the study's subjects. A virtualized interview guideline is the tool being used. The results of this investigation are as follows: 1) Students' opinions of the Kampus Mengajar programme, which focuses on literacy, numeracy, and technology adaptation, are favourable; they understand the program's ideas, goals, and method of implementation; and there has been an improvement in learning outcomes across all target schools, albeit to varying degrees. 2) The deficiencies found include the lack of socialisation to the target school, which makes it difficult for teachers to understand the program's concept, as well as the delay in allocating living expenses, the existence of nominal inconsistencies that students were informed of at the start of the programme, and the existence of inconsistencies in the university course conversion system.